‘I Thought Asking the Experts of the Board First before Turning at the Unctuous salesmen.’ Requesting Special Field Related Advice and Information on Online Communities - Salmela, Eveliina (Facultas, 2022)
This study focuses on requesting and sharing specialized information on online communities. The aim was to find out how requesting and receiving special field related information function on online discussions about heat pumps in Finland. The data consists of 300 message threads collected from two Finnish discussion boards, Lampopumput.info (heatpumps.info) and Suomi24.fi (Finland24.fi). The data was analyzed using discourse analytic methods and pragmatic concepts such as speech acts, politeness, relevance and humor. The results demonstrate the sense of community as an important part of the specialized communication in online peer support discussions. The appropriate wording of the messages, politeness and giving one’s personal contribution to the community are important factors in conveying information through online communities. Online peer discussions have several different communicative goals, such as requesting and offering technical support, requesting advice, sharing experiences and expressing views and opinions. Users use different platforms to carry out these goals. Requesting advice and sharing information were emphasized on the discussion board that requires registration from the contributors. The discussion board, which required registration, was more specific to the topic and community like. There were more direct answers and dialog between the users than on the anonymous discussion board. On the open discussion board, which did not require registration, writers expressed more their own personal views and opinions and discussed especially about topics related to the purchase situation.
Keywords: Asynchronous online discussion; technical communication; peer advice; requesting advice; online communities; fi=Viestintätieteet|en=Communication Studies|